Organization of Interaction Between A Group of Unmanned Aerial Vehicles and A Ground Control Station - Qodirov Sodiq Salimovich; Rayimov G‘ayrat Raxmatullayevich (Scientific Trends, 2025)
This paper examines the use of civilian UAV swarms in urban environments, focusing on improving communication through a specialized relay quadcopter with a narrow-beam antenna. Swarm operation offers cost efficiency and reliability but requires precise navigation and stable communication amid urban interference. By combining navigation data from all swarm elements, the system achieves accurate positioning to guide the relay’s antenna, enhancing range, interference resistance, and security of the link to the ground control station. The study also reviews antenna control systems and communication standards like WiMax. Although relay use may cause data delays and risks from single-point failure, redundancy strategies help maintain reliable communication, making the approach promising for urban UAV applications
Keywords: Unmanned Aerial Vehicles (UAVs), UAV swarm, narrow-beam antenna, autonomous flight, navigation system, radio communication, urban environment, swarm coordination, WiMax technology, communication relay, interference resistance, payload, flight control, data transmission, redundancy.